2002
DOI: 10.1007/s00384-002-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's disease: in defense of a microvascular aetiology

Abstract: Proving cause and effect will always be a difficult task given the self-perpetuating nature of the inflammatory and coagulation cascades and our inability at present to identify persons who subsequently develop Crohn's disease at a point prior to mucosal inflammation. Results to date however, are supportive of each of these factors, alone or in combination playing an integral part in the development of microvascular ischaemia, a pathological process which appears to precede the classic changes which characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 85 publications
(89 reference statements)
3
47
0
7
Order By: Relevance
“…[1][2][3][4]24 In contrast, the role of microvascular endothelial barrier in defense of intestinal homeostasis is less recognized and investigated despite the fact that it: (1) is essential for capillary blood flow, oxygen and nutrient delivery; (2) serves as a 'gatekeeper' preventing the extravasation of circulating leukocytes and other inflammatory cells and proteins into the mucosa; and (3) has a major role in innate immune response, by synthesis and release of pro-inflammatory cytokines. 10,[25][26][27] We found that young Ga-i2 À/À mice in early stages of spontaneously developing UC demonstrate areas of colonic mucosa with perivascular edema in the lamina propria covered by uninterrupted normal layer of surface epithelial cells. Older Ga-i2 À/À mice with advanced stage of UC had focal areas of perivascular edema containing leukocytes and a continuous layer of surface epithelial cells outside the areas of erosions and ulcers.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…[1][2][3][4]24 In contrast, the role of microvascular endothelial barrier in defense of intestinal homeostasis is less recognized and investigated despite the fact that it: (1) is essential for capillary blood flow, oxygen and nutrient delivery; (2) serves as a 'gatekeeper' preventing the extravasation of circulating leukocytes and other inflammatory cells and proteins into the mucosa; and (3) has a major role in innate immune response, by synthesis and release of pro-inflammatory cytokines. 10,[25][26][27] We found that young Ga-i2 À/À mice in early stages of spontaneously developing UC demonstrate areas of colonic mucosa with perivascular edema in the lamina propria covered by uninterrupted normal layer of surface epithelial cells. Older Ga-i2 À/À mice with advanced stage of UC had focal areas of perivascular edema containing leukocytes and a continuous layer of surface epithelial cells outside the areas of erosions and ulcers.…”
Section: Discussionmentioning
confidence: 69%
“…A number of clinical and experimental studies showed oxygen deprivation of colonic epithelial cells in inflammatory bowel disease (IBD). 5,10,25,36 Moreover, prevention of hypoxia by heparin 37 or endothelin-1 receptor antagonist 38 significantly reduced the degree of mucosal injury and inflammatory response. In addition to endothelial damage and intravascular congestion, our present study demonstrated hypoxia in colonic surface epithelial cells that preceded the enhanced colonic EP.…”
Section: Endothelial Damage In Ulcerative Colitismentioning
confidence: 96%
“…In the present example of colitis, it was proposed that the vasculitis associated with such diseases as Crohn disease contributed significantly to the establishment and maintenance of chronic inflammation (1,4). In addition, there is evidence for a complex system of bidirectional crosstalk between hypoxia and inflammation, since cytokines liberated during inflammation (e.g., IL-1, IFN-β, TNF-α) may regu- vehicle-treated WT), such differences were enhanced in conditional Vhlh mutant animals exposed to TNBS in regard to ITF, MDR1, and CD73 ( † P ≤ 0.05 vs. TNBS-treated WT, ‡ P ≤ 0.05 vs. vehicle-treated Vhlh mutants).…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies suggest a close association of inflammation and hypoxia at the tissue level. In Crohn disease, a chronic intestinal inflammatory process that is, at least in part, characterized by marked abnormalities of gut barrier function, microvascular disturbances have been consistently demonstrated (1)(2)(3). Consequently, observations from both human disease (4,5) and experimental colitis (6,7) suggest the presence of colonic hypoxia and its significance in the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Doenças intestinais inflamatórias frequentemente podem levar a episódios de isquemia, como a Doença de Crohn e isquemia aguda mesentérica (HAGLUND; BERGQVIST, 1999;THORNTON;SOLOMON, 2002). Além disso, I/R-i de vasos intestinais são recorrentes em pacientes hospitalizados, especialmente aqueles que estão nas unidades de terapias intensivas (OLDENBURG et al, 2004).…”
Section: Isquemia E Reperfusão Intestinal (I/r-i)unclassified